Cholesterol contributes to dopamine-neuronal loss in MPTP mouse model of Parkinson's disease: Involvement of mitochondrial dysfunctions and oxidative stress. - Rajib Paul; Amarendranath Choudhury; Sanjeev Kumar; Anirudha Giri; Rajat Sandhir; Anupom Borah (PLoS ONE)
Hypercholesterolemia is a known contributor to the pathogenesis of Alzheimer's disease while its role in the occurrence of Parkinson's disease (PD) is only conjecture and far from conclusive. Altered antioxidant homeostasis and mitochondrial functions are the key mechanisms in loss of dopaminergic neurons in the substantia nigra (SN) region of the midbrain in PD. Hypercholesterolemia is reported to cause oxidative stress and mitochondrial dysfunctions in the cortex and hippocampus regions of the brain in rodents. However, the impact of hypercholesterolemia on the midbrain dopaminergic neurons in animal models of PD remains elusive. We tested the hypothesis that hypercholesterolemia in MPTP model of PD would potentiate dopaminergic neuron loss in SN by disrupting mitochondrial functions and antioxidant homeostasis. It is evident from the present study that hypercholesterolemia in naïve animals caused dopamine neuronal loss in SN with subsequent reduction in striatal dopamine levels producing motor impairment. Moreover, in the MPTP model of PD, hypercholesterolemia exacerbated MPTP-induced reduction of striatal dopamine as well as dopaminergic neurons in SN with motor behavioral depreciation. Activity of mitochondrial complexes, mainly complex-I and III, was impaired severely in the nigrostriatal pathway of hypercholesterolemic animals treated with MPTP. Hypercholesterolemia caused oxidative stress in the nigrostriatal pathway with increased generation of hydroxyl radicals and enhanced activity of antioxidant enzymes, which were further aggravated in the hypercholesterolemic mice with Parkinsonism. In conclusion, our findings provide evidence of increased vulnerability of the midbrain dopaminergic neurons in PD with hypercholesterolemia.